Global SUMOylation is a molecular mechanism underlying hypothermia-induced ischemic tolerance - Lee, Yang-ja; Mou, Yongshan; Klimanis, Dace; Bernstock, Joshua D.; Hallenbeck, John M. (Frontiers in Cellular Neuroscience, 2014)
The molecular mechanisms underlying hypothermic neuroprotection have yet to be fully elucidated. Herein we demonstrate that global SUMOylation, a form of post-translational modification with the Small Ubiquitin-like MOdifer, participates in the multimodal molecular induction of hypothermia-induced ischemic tolerance. Mild (32°C) to moderate (28°C) hypothermic treatment(s) during OGD (oxygen-glucose-deprivation) or ROG (restoration of oxygen/glucose) increased global SUMO-conjugation levels and protected cells (both SHSY5Y and E18 rat cortical neurons) from OGD and ROG-induced cell death. Hypothermic exposure either before or after permanent middle cerebral artery occlusion (pMCAO) surgery in wild type mice increased global SUMO-conjugation levels in the brain and in so doing protected these animals from pMCAO-induced ischemic damage. Of note, hypothermic exposure did not provide an additional increase in protection from pMCAO-induced ischemic brain damage in Ubc9 transgenic mice, which overexpress the sole E2 SUMO conjugating enzyme and thereby display elevated basal levels of global SUMOylation under normothermic conditions. Such evidence suggests that increases in global SUMOylation are critical and may account for a substantial part of the observed increase in cellular tolerance to brain ischemia caused via hypothermia.